A comparative analysis of the value of recreation in six contrasting Nordic landscapes using the travel cost method. (September 2022) - Juutinen, Artti; Immerzeel, Bart; Pouta, Eija; Lankia, Tuija; Artell, Janne; Tolvanen, Anne; Ahtiainen, Heini; Vermaat, Jan
Abstract: Nordic landscapes provide recreational benefits to local, national, and international visitors. Nordic countries are, however, actively promoting a green shift towards the bioeconomy (that is, an intensification of agriculture and forestry), which may come at the cost of other benefits of Nordic landscapes, such as recreation. Information on recreational benefits and their monetary value is therefore required to outline a more comprehensive bioeconomy policy. For this paper, we estimated the benefits associated with the recreational use of six contrasting landscapes from four Nordic countries in their current environmental conditions, using a travel cost model, with data from a standardised survey of inhabitants and visitors. We found a large variation in the monetary estimates of the current annual recreational benefits from these landscapes, with a variation from 3.1 to 120.8 million € per landscape. We found that different characteristics of these landscapes, such as the visitor structure and visitors' perceptions of the environmental quality, influence the estimated recreational value. Among the environmental characteristics we tested, we found that water quality and the proportion of nature conservation areas influence the recreational benefits, and need to be considered when making land use and management decisions. Furthermore, it is important that a sustainable bioeconomy policy is developed and implemented in such a way that the potentially negative effects of intensified agriculture and forestry on recreational possibilities are avoided.